2008
DOI: 10.1071/rd07153
|View full text |Cite
|
Sign up to set email alerts
|

Female reproductive tract fluids: composition, mechanism of formation and potential role in the developmental origins of health and disease

Abstract: The oviduct and uterus provide the environments for the earliest stages of mammalian embryo development. However, little is known about the mechanisms that underlie the formation of oviduct and uterine fluids, or the extent to which the supply of nutrients via these reproductive tract tissues matches the nutrient requirements of early embryos. After reviewing our limited knowledge of these phenomena, a new experimental paradigm is proposed in which the epithelia lining the endosalpinx and endometrium are seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(134 citation statements)
references
References 57 publications
1
124
0
9
Order By: Relevance
“…The oviductal fluid contains amino acids, proteins, simple, and complex carbohydrates, ions, lipids, and phospholipids. Some of these components are metabolic substrates, such as lactate, pyruvic acid, amino acids, and glucose, whose levels differ from those present in the uterine fluid and the serum (Leese 1988, Leese et al 2008, Hugentobler et al 2010. Experimental evidence indicated that ion concentrations in oviductal fluid also differ from those of serum, suggesting that the oviductal epithelium modulates ion levels (Leese 1988, Leese et al 2008, Hugentobler et al 2010.…”
Section: Reproduction (2015) 149 R1-r14mentioning
confidence: 99%
See 3 more Smart Citations
“…The oviductal fluid contains amino acids, proteins, simple, and complex carbohydrates, ions, lipids, and phospholipids. Some of these components are metabolic substrates, such as lactate, pyruvic acid, amino acids, and glucose, whose levels differ from those present in the uterine fluid and the serum (Leese 1988, Leese et al 2008, Hugentobler et al 2010. Experimental evidence indicated that ion concentrations in oviductal fluid also differ from those of serum, suggesting that the oviductal epithelium modulates ion levels (Leese 1988, Leese et al 2008, Hugentobler et al 2010.…”
Section: Reproduction (2015) 149 R1-r14mentioning
confidence: 99%
“…The presence of adequate levels of bicarbonateand calcium seems to be essential in regulating sperm capacitation, motility, and acrosome reaction (Rodriguez-Martinez 2007, Leese et al 2008, Abouhaila & Tulsiani 2009, Lishko et al 2012. Hyaluronan and sulfated glycosaminoglycans, such as heparin, have been detected in oviductal fluid from different mammalian species (Kawakami et al 2000, Tienthai et al 2000, Bergqvist & Rodríguez-Martínez 2006.…”
Section: Oviductal Secretion and Sperm Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility could be that FF G-CSF provides the embryo with crucial information on how to repair itself (16). The FF itself could be involved in the complex dialogue that leads to implantation and could transmit messages directly to the fallopian tube and to the uterus in fertile patients (28). However, it is difficult to imagine the FF cytokines, which are known to act locally, influencing directly the receptivity of the uterus, which is far from the ovary.…”
Section: Resultsmentioning
confidence: 99%